Understanding Teachers' and Students' Use and Attitudes of Web 2.0 in ESL Classrooms at the American University of Sharjah - Al-Ali, Sebah (2010)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Sebah Al-Ali Entitled, "Understanding Teachers' and Students' Use and Attitudes of Web 2.0 in ESL Classrooms at the American University of Sharjah," May 2010. Available are both Hard and Soft Copies of the Thesis.